Analysis of the carbonatation process of nanosized Ca(OH)2 particles synthesized by exchange ion process. Issue 1 (March 2016) - Taglieri, Giuliana; Felice, Benito; Daniele, Valeria; Volpe, Roberto; Mondelli, Claudia
Calcium hydroxide nanoparticles in hydro-alcoholic dispersion are introduced as an effective conservation material for carbonatic substrates, thanks to their promising carbonation efficacy in ambient air. However, the current methods to synthesize such dispersions are characterized by some drawbacks that strongly limit applications. The aim of this work is to investigate structure, morphology and carbonatation efficacy of calcium hydroxide nanoparticles in aqueous suspension, produced by our alternative and original method of synthesis, based on the use of an ion exchange resin. Actually, the method allows to produce pure, nanosized and reactive Ca(OH)2 particles, operating at room temperature, without intermediate steps to eliminate undesired compounds, drastically reducing the time, and with a potential ability to be easily scaled up to provide larger amounts of nanoparticles. By X-ray diffraction techniques, we have investigated reactivity of the synthesized nanoparticles, in relation to the carbonatation process in air, by varying the suspension concentration. Preliminary results on the kinetics of the carbonatation process are presented too. Morphological analysis, performed by transmission electron microscopy, shows both hexagonal particles, often quarries, of side dimensions less than 100 nm, and spherical particles (<50 nm).